Dealing with Relational and Social Challenges After Child Soldiering: Perspectives of Formerly Recruited Youth and Their Communities in Northern Uganda. (20th November 2015) - Schiltz, Julie; Vindevogel, Sofie; Broekaert, Eric; Derluyn, Ilse
Abstract: The reintegration of formerly recruited youth typically engenders a range of relational and social challenges, affecting both formerly recruited youth and the communities to which they return. Yet, research rarely studies the perspectives of community members, hampering the design of much‐needed community‐based interventions. This study aimed to understand how communities in northern Uganda experience and deal with relational and social challenges during the reintegration of youths who were formerly recruited into the Lord's resistance army (LRA). The study was undertaken in 2012 in Lira district. Participatory Ranking Methodology (PRM) was conducted with 267 participants, of whom 49 were formerly recruited youths. The results show five themes that give insight into how communities experience and handle relational and social challenges in the reintegration of formerly recruited youth: (i) letting go of fear, (ii) getting used to life after captivity, (iii) resentment and forgiveness, (iv) reducing insults and nicknaming and (v) coping with ongoing relational and social challenges. We discuss how formerly recruited youths and other community members frame relational and social challenges differently, and value similar resources for different reasons. The results of this study suggest that multiple experiences of and perspectives on relational and social challenges following child soldiering should be taken into account to develop interventions that are supported and valued by the community. Furthermore, interventions should draw upon the strategies that communities have already developed in response to relational and social challenges. Copyright © 2015 John Wiley & Sons, Ltd.